Randomised controlled trials in Scandinavian educational research. Issue 3 (3rd July 2018) - Pontoppidan, Maiken; Keilow, Maria; Dietrichson, Jens; Solheim, Oddny Judith; Opheim, Vibeke; Gustafson, Stefan; Andersen, Simon Calmar
ABSTRACT: Background : The Scandinavian countries have a long history of implementing social interventions, but the interventions have not been examined using randomised controlled trials until relatively recently compared with countries like the United States and the United Kingdom. Purpose : The purpose of this paper is to examine the history of randomised controlled trials in Scandinavian compulsory schools (grades 0–10; pupil ages 6–15). Specifically, we investigate drivers and barriers for randomised controlled trials in educational research and the differences between the three Scandinavian countries Denmark, Norway, and Sweden. Methods : To locate relevant trials, we performed a systematic search of four bibliographic databases and a search for grey literature. Results were combined with trials located through direct contact with researchers and government officials. A trial was included if one or more interventions were randomly assigned to groups of students and carried out in a school setting with the primary aim of improving the academic performance of children aged 6–15 in grades 0–10 in Denmark, Norway, or Sweden. We included both conducted and ongoing trials. Publications that seemed relevant were screened based on full-text versions. Data extraction included information from the included studies on grade level, study period, sample size (N), project owner, funding source, and theme. In addition, we conducted two semi-structured interviews by phone or in person with central employees in funding agencies and ministries and 25 correspondences with researchers and policymakers. Findings and conclusion : RCTs in grades 0–10 were few in all of Scandinavia until about 2011, after which there was an increase in all three countries, although at different rates. The largest number of trials has been conducted in Denmark, and the increase is more marked in Denmark and Norway compared with Sweden. International trends towards more impact evaluations and results from international comparisons such as PISA have likely affected the development in all countries, but while many trials in Denmark and Norway are the result of policy initiatives, only one such example in Sweden was identified. We believe the lack of government initiatives to promote RCTs in Sweden is the most likely explanation for the differences across the Scandinavian countries. Funding and coordination from the government are often crucial for the implementation of RCTs and are likely more important in smaller countries such as the Scandinavian ones. Supporting institutions have now been established in all three countries, and we believe that the use of RCTs in Scandinavian educational research is likely to continue.